VALUATION OF LONG TERM CARE (LTC) HEALTH INSURANCE CONTRACT USING MULTISTATE MODEL - Adhitya Ronie Effendi (MATEMATIKA, 2009)
In this paper, we are using multistate model to evaluate Long Term Care (LTC) health insurance contract. Some products in LTC contract such as stand alone Annuity, LTC as a rider benefit, Enhanced pension and Insurance package are discussed. We use Discrete Time Markov Chains (DTMC) to model health status of each of the patients. Every time, a patient is exposed to one of the status that already set in the status space, for example: health, ill and death. We also consider evaluating premiums and reserves generated by this model which also useful for the practioneers and insurance companies.